Scottish administrative law - McFadden, Jean (Law essentials., 2006)
A concise overview of the different facets of this branch of public law. From judicial review to ombudsmen, and from ultra vires to natural justice, discover how law governs the activities of the government's administrative agencies. Helping to orientate you within the subject with an introduction and explanations of the doctrines of the constitution and the structure of the government, before moving on to how administrative law is currently practiced in Scotland. End-of-chapter summaries of Essential Facts and Essential Cases will help you to learn and revise the key points.